La yuxtaposición de sistemas en América Latina y sus consecuencias - Noejovich, Héctor Omar (2006)
This essay aim to set new hypothesis for Latin American’s development problem; the analysis is focused from “the encounter of two worlds” to the present. The generaland main hypothesis is a sort of “clutched” between the “Pre-Columbian System” and the “European System” and resulted in a so-called “Colonial System”. This “Colonial System” is defined as juxtaposition of systems and it has been suffering Western influence like a kind of “external shock” but keeping to an already hybrid system, wherein an inertial dynamic and not a dialectic one has been the main trait. The whole historical process is explained under such a point of view.